1994
DOI: 10.1063/1.466264
|View full text |Cite
|
Sign up to set email alerts
|

Rotationally resolved photoionization of polyatomic hydrides: CH3, H2O, H2S, H2CO

Abstract: Combined theoretical and experimental studies of rotationally resolved photoelectron spectra for single-photon ionization of the outermost valence orbitals of H 2 0, H 2 S, H 2 CO, and CH 3 are reported. Agreement between calculated and measured spectra is very encouraging. Both show that photo ionization dynamics is very molecular in origin for H 2 0, H 2 S, and H 2 CO but quite atomiclike for CH 3 . Parity selection rules and the angular momentum composition of the photoelectron are used to illustrate the dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 37 publications
2
18
0
Order By: Relevance
“…There are cases when it can be advantageous to determine the intensities of specific N 0 →N ϩ transitions and these have been discussed at length. 9,13,19,53 In the present study, the fluorescence measurements provide considerable insight and sufficient detail into the angular momentum transfers that occur during the ionization process. As a result, the data yield information on the energy-dependent angular momentum composition of the photoelectron matrix element with great clarity.…”
Section: Resultsmentioning
confidence: 99%
“…There are cases when it can be advantageous to determine the intensities of specific N 0 →N ϩ transitions and these have been discussed at length. 9,13,19,53 In the present study, the fluorescence measurements provide considerable insight and sufficient detail into the angular momentum transfers that occur during the ionization process. As a result, the data yield information on the energy-dependent angular momentum composition of the photoelectron matrix element with great clarity.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Cooper minima 4 -8 and shape resonances [9][10][11][12][13][14][15][16] typically extend over a range of 10-50 eV, and it is hence desirable to study rotational distributions over a comparable range. Unfortunately, rotationally resolved photoelectron experiments are typically limited to the near-threshold region [17][18][19][20][21][22][23][24][25][26][27] ͑although recent progress has resulted in partially rotationally resolved photoelectron data over a significant range 28,29 ͒. In our previous studies, we demonstrated that dispersed fluorescence is capable of determining energy-dependent aspects of rotationally resolved effects in molecular photoionization over the broadest energy range.…”
Section: Introductionmentioning
confidence: 99%
“…Note that no parity selection rules relating Ap, AN, and d are obtained for photoionization of symmetric tops, since the partial wave components of each electronic continuum have different phase factors (43). However, Equation 25 does reveal that/t + 2 ---_ AK and p + 2 = + (K+ + K3.…”
Section: Ionization Of Symmetric Topsmentioning
confidence: 99%
“…In contrast, the above analysis (56,57) shows that these type a transitions arise quite naturally in a correct quantitative www.annualreviews.org/aronline Annual Reviews description of the direct molecular photoionization process itself and a polarization-induced autoionization mechanism need not be invoked. Figure 8 shows the (a) measured and (b) calculated rotationally resolved ZEKE-PFI spectra of H2CO for single-photon ionization of the nonbonding 2b2 orbital by coherent VUV radiation (43). The calculated spectrum assumes a rotational temperature of 7 K and a photoelectron kinetic energy of 50 meV and is convoluted with a Gaussian detection function with an FWHM of 1.8 cm-1.…”
Section: Single-photon Ionization Of Nonlinear Molecules (H20 H2co mentioning
confidence: 99%